LEGAL RESPONSIBILITY IN CONTRACTUAL RELATIONS BETWEEN BANKS AND CUSTOMERS FOR CREDIT AGREEMENTS (DECISION STUDY NUMBER: 964/Pdt.G/2025/PN.Mdn) - Nora Salsabillah; Nurhilmiyah (International Journal of Cultural and Social Science, 2026)
This research aims to analyze legal responsibility in contractual relations between banks and customers regarding credit agreements and examine the judge's considerations in Decision Number 964/Pdt.G/2025/PN.Mdn at the Medan District Court. The problem stems from a default in the Home Ownership Credit (KPR) agreement between the debtor and PT Bank Tabungan Negara (Persero) Tbk which resulted in bad credit and demands for repayment of the remaining debt along with the execution of collateral rights dependants. The research method used is normative legal research with a legislative, conceptual and case approach. The results showed that the legal relationship between banks and customers is based on a valid agreement according to the Civil Code and is binding on the parties as law. The panel of judges considered that the debtor was found to have defaulted on the fact that it did not fulfil the obligation to pay the instalments in accordance with the agreement, and was thus punished to pay off the remaining obligations together with interest and fines and to give the creditor the right to execute the security. The ruling reflects the application of the principles of legal certainty and legal protection in the practice of banking credit agreements.